Evaluation of the Nutritive Value of the African Giant Land Snail, Archachatina (Calachatina). - Imevbore, Emmanuel Abayomi (Obafemi Awolowo University, 2014)
In order to assess the nutritive value of the African giant land Snail (Archachatina marginata), a comparison between its meat and some conventional sources of animal protein - beef, broiler meat, mutton, pork, goat meat and two types of fish (Tilapia macrocephala and Clarias lazera) was made. The proximate composition, fatty acid, amino acid and mineral analyses, as well as cholesterol content of the samples were used as criteria for comparison.